Sex dimorphic regulation of osteoprogenitor progesterone in bone stromal cells. (November 2017) - Kot, Alexander; Zhong, Zhendong A; Zhang, Hongliang; Lay, Yu-An Evan; Lane, Nancy E; Yao, Wei
Abstract : Increasing peak bone mass is a promising strategy to prevent osteoporosis. A mouse model of global progesterone receptor (PR) ablation showed increased bone mass through a sex-dependent mechanism. Cre-Lox recombination was used to generate a mouse model of osteoprogenitor-specific PR inactivation, which recapitulated the high bone mass phenotype seen in the PR global knockout mouse mode. In this work, we employed RNA sequencing analysis to evaluate sex-independent and sex-dependent differences in gene transcription of osteoprogenitors of wild-type and PR conditional knockout mice. PR deletion caused marked sex hormone-dependent changes in gene transcription in male mice as compared to wild-type controls. These transcriptional differences revealed dysregulation in pathways involving immunomodulation, osteoclasts, bone anabolism, extracellular matrix interaction and matrix interaction. These results identified many potential mechanisms that may explain our observed high bone mass phenotype with sex differences when PR was selectively deleted in the MSCs.